The Effects of Perceived Identity Threat and Realistic Threat on the Negative Attitudes and Usage Intentions Toward Hotel Service Robots: The Moderating Effect of the Robot’s Anthropomorphism - Huang, Hsien-Long; Cheng, Li-Keng; Sun, Pi-Chuan; Chou, Szu-Jung (International journal of social robotics, 2021)
The use of social robots in service scenarios (e.g. in hotels) is expected to increase. Research has indicated that realistic threat and identity threat contribute to prejudice, discrimination, and conflict. Therefore, designing smart robots that can understand user needs and provide prompt service is critical. This study aimed to explore the relationships among perceived threat, negative attitudes toward robots, and usage intention, and to discuss how anthropomorphism moderates the relationship between negative attitudes and usage intention toward robots. We hypothesized that realistic threat and identity threat positively influence negative attitudes toward social robots; such negative attitudes have negative effects on usage intention; and anthropomorphism positively moderates said effect. A between-subjects factorial research design was employed; participants were randomly assigned to one of two conditions of robot anthropomorphic appearance. The stimuli were two pictures of service robots—one with a humanoid appearance and one without. After viewing one of the stimuli, participants filled in a questionnaire that assessed the realistic threat, identity threat, negative attitudes, and usage intention. When participants perceived the robot’s appearance to be highly anthropomorphic, their negative attitudes toward it had a stronger negative effect on their usage intention than when they considered the appearance less anthropomorphic. Both identity threat and realistic threat significantly increased negative attitudes toward the robots; thus, the public’s willingness to use these robots would be negatively affected. This study recommends that robotics companies consider how to decrease people’s perceived realistic and identity threats as well as adjust robots’ anthropomorphic appearance to people’s tastes.